Vaginal lavage fluid can serve as a reliable method for early screening of endometrial cancer: a proof-of-concept study - Li, Yibing; Ren, Ping; Huang, Jiazhen; Tan, Shuang; Wang, Ning (Frontiers in Oncology, 2026)
BackgroundEndometrial cancer (EC) is one of the malignant tumors in the female reproductive system, and effective screening is urgently needed to reduce mortality. At present, the main screening method for endometrial cancer is ultrasound combined with curettage and pathological examination. We plan to explore a non-invasive, convenient, and low-cost new screening method for EC, providing a more convenient way for early screening of EC.MethodsWe included a total of 11 patients with stage IA EC, and collected 8-10ml of blood, pathological paraffin sections, and vaginal lavage fluid for each patient. The collection of vaginal lavage fluid was performed before the patient’s curettage or hysteroscopy for pathological examination. And perform high-throughput sequencing and further analysis on it.ResultsIn 11 cases with matched tumor and blood tissues, the extracted ctDNA concentration was significantly higher in vaginal lavage fluid than in plasma. The average and median MAF of different samples from paired tissue patients were significantly higher in vaginal lavage supernatant and sediment than in plasma. The types of genomic changes in the supernatant of vaginal lavage fluid are relatively consistent with those in the sediment and tumor tissue samples, but significantly different from those in the plasma. In addition, among the six most frequently mutated genes in this study, the consistency between vaginal lavage fluid supernatant and vaginal lavage fluid precipitation and tumor tissue genomic changes was significantly higher than in plasma. According to the results of 11 cases that provided tumor tissue samples, the genomic changes detected between the supernatant or precipitate of vaginal lavage fluid and tumor tissue were significantly consistent compared to those detected between tumor tissue and plasma. The potential targets for targeted treatment of endometrial cancer (KRAS, PIK3CA, MLH1, MSH6, POLE, PTEN) showed more significant changes in the supernatant of vaginal lavage fluid.ConclusionThe supernatant/precipitate of vaginal lavage fluid has significant clinical significance for early screening of endometrial cancer and may also have potential clinical value in guiding targeted therapy and evaluating prognosis. Vaginal lavage fluid gene sequencing may serve as a new method for initial screening of endometrial cancer.